A Novel Polysaccharide Depolymerase Encoded by the Phage SH-KP152226 Confers Specific Activity Against Multidrug-Resistant Klebsiella pneumoniae via Biofilm Degradation - Wu, Yunqiang; Wang, Rui; Xu, Mengsha; Liu, Yanan; Zhu, Xianchao; Qiu, Jiangfeng; Liu, Qiming; He, Ping; Li, Qingtian (Frontiers in Microbiology, 2019)
The increasing prevalence of infections by multidrug-resistant Klebsiella pneumoniae necessitates the development of alternative therapies. Here, we isolated, characterized and sequenced a K. pneumoniae bacteriophage (SH-KP152226), which specifically infects and lyses K. pneumoniae capsular type K47. Phage SH-KP152226 contains a genome of 41,420 bp that encodes 48 predicted proteins. Among them, Dep42, the gene product of ORF42, is a putative tail fiber protein and hypothetically possesses depolymerase activity. We demonstrated that recombinant Dep42 showed specific enzymatic activities on the depolymerization of the K47 capsule of K. pneumoniae and was able to significantly inhibit biofilm formation and/or degrade formed biofilms. We also showed that Dep42 could enhance polymyxin activity against K. pneumoniae biofilms through the combination of depolymerase and antibiotics. These results suggest that the identified novel depolymerase Dep42 encoded by phage SH-KP152226 combined with antibiotics may represent a promising strategy to combat infection by drug-resistant and biofilm-forming K. pneumoniae.